Unsettling Monstrosity in Rhymes for Young Ghouls. Issue 1 (1st June 2019) - Neely, Sol
Abstract : Rhymes for Young Ghouls (2014), written and directed by Mi'kmaq filmmaker Jeff Barnaby, is primarily presented as a residential school "revenge fantasy." Some critics and reviewers of the film value it for its pedagogical possibilities, arguing that the film occasions opportunity for dialogue between Indigenous and non-Indigenous audiences about the legacies of the residential school system. Yet, numerous decolonial scholars and activists understand that dialogue alone cannot effect the quality of decolonial justice needed in the wake of genocide. This article approaches the film as a saturated phenomenon and examines the kinds of radical phenomenological transformation that must occur, especially among non-Indigenous audiences, for decolonial imperatives to become legible. Beyond developing a more comprehensive historical panorama of the violence and legacies of the residential school system, this article calls for a kind of translation of experience occasioned by the film, one that dramatically subverts and transforms modalities of consciousness on which coloniality is predicated.